PENGARUH FREE CASH FLOW, PROFITABILITAS, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KEBIJAKAN HUTANG - Mahsunah, Tutik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is to test the influence of free cash flow, profitability, and institutional ownership to the account receivable policy on manufacturing companies which are listed in Indonesia Stock Exchange (IDX). This research uses quantitative method and it categorizes as comparative causal research. The population is manufaturing companies which are listed in Indonesia Stock Exchange from 2008 to 2012. 20 companies have been selected as samples by using purposive sampling method. The data is secondary data. The data collection method uses library study and documentation. The data has been obtained from Indonesia Stock Exchange official sites (IDX) i.e.: www.idx.co.id. The multiple regression technique is used as data analysis technique. The result of research shows that free cash flow has positive influence to the account receivable policy, profitability has negative influence to the account receivable policy. Institutional ownership has postive influence to the account receivable policy. While the capability of free cash flow, profitability, and institutional ownership in explaining the account receivable policy is 65.9% the remaining 34.1% is explained by other variables outside the regression model. Keywords: free cash flow, profitability, institutional ownership, account receivable policy.